(untitled) (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The Arabic language constitutes the most important factors upon which our nation is based, in addition to other factors such as history, economics, science, and others, and it constitutes an essential element in building the identity of every individual of this nation. What increases the importance of this language among Arabs and Muslims is that it is the language of the Holy Qur’an. It is not possible to properly understand the Book of God and taste its linguistic and declarative miracle except by reading it in Arabic, just as the rich heritage of Islamic sciences and the most important books is written in Arabic, and from here learning Arabic was a goal for all Muslims, as Arabic is the longest-lived language and closest to the mother tongue, so there is no language It has the same heritage as the Arabic language, and it is universal like its religion, which is guidance for all people. Hence the researcher’s choice of the axis tagged with: (The Arabic language and its role in building society and cultural heritage) The research was divided, God willing, into an introduction, a preface, and two sections, as follows: 1. The first topic: The role of the Arabic language in building society. 2. The second topic: The role of language in highlighting the cultural heritage of the nation. Then the conclusion, sources and references.